Lipid Dysmetabolism in Canine Chronic Liver Disease: Relationship Between Clinical, Histological and Immunohistochemical Features - Verena Habermaass; Yuki Takami; Takeshi Izawa; Francesca Abramo; Corrado Biolatti; Veronica Marchetti (Veterinary Sciences)
Chronic liver diseases (CLDs) in dogs are progressive conditions that often lead to liver failure. Metabolic dysfunctions such as cholestasis, obesity, hyperlipidemia, and endocrine disorders play a key role in human liver diseases like MASLD (Metabolic Dysfunction Associated Steatotic Liver Disease) and MASH (Metabolic Dysfunction Associated Steatohepatitis), but their significance in canine CLDs is poorly understood. This study aims to evaluate the association between hepatic lipid accumulation and inflammation or fibrosis in canine CLDs and its potential association with metabolic dysfunctions. Sixteen client-owned dogs with CLDs were assessed for clinical data, histological features, and liver immunohistochemistry (IHC). Histological and IHC markers of inflammation (Iba-1, iNOS, NF-κB), fibrosis (CD206, α-SMA, Sirius Red), and lipid accumulation (adipophilin) were assessed to identify correlations with clinical conditions. The applied markers showed effectiveness in their use on canine liver tissue. Adipophilin-marked lipid accumulation correlated positively with inflammatory markers, indicating a link between steatosis and inflammation. Metabolic dysfunctions were linked to hepatic lipid accumulation and inflammation. These findings show a potential alignment of canine CLDs with human MASLD/MASH, where lipid-induced inflammation drives disease progression. IHC markers could effectively assess these processes, suggesting potential for guiding diagnostics and therapies, though further research is needed to clarify clinical associations.